Perancangan Sistem Penentuan Lead Time Produksi Berdasarkan Kapasitas dan Waktu Baku pada PT. X - Kevin Kusuma Prawiro; Prayonne Adi (Jurnal Titra, 2021)
PT. X is a subsidiary of PT Astra Otoparts engaged in the automotive industry inproducing motorcycle chains, engine chains, filters, and accessories for motorbikes. PT. X has 2customer chain products, namely OEM (Original Equipment Market) products which includeAstra Honda Motor (AHM), Yamaha, Kawasaki, and Suzuki. RM Products (ReplacementMarket) which include Honda Genuine Part (HGP) and Yamaha Genuine Part (YGP). The chainof OEM products is a chain that will be installed directly on a motorcycle during the assemblyprocess. The RM product chain is a spare parts chain that will be marketed in motorcycledealers. Determining the standard time and production capacity of each process aims todetermine the production lead time. Production lead time is needed by the company to determinea product from the start of the raw material being processed to the end of being a chain product.The results of the calculation of the standard time of each process can be analyzed as the cause ofthe delay in product distribution to the customer. The results of this study are used to determinethe production lead time for a certain period with the number of stock components, the numberof chain stocks used for production plans for a certain period. The production plan uses data fromthe calculation of the standard process time and process capacity used to determine theproduction lead time.